The Relationship between Prenatal Gentle Yoga and the Level of Anxiety of Primigravid Pregnant Women in the Third Trimester in Facing Childbirth at the Juliana Dalimunthe Clinic - Saragih, Rismaida; Siregar, Siti Arfah (International Journal of Public Health Excellence (IJPHE), 2023)
Worry is reaction general and incompetence in face problem, yes, happened to whom course, incl. Mother, the third trimester of pregnancy that will be face labor. The impact it caused on the victim, namely depression post-birth, birth prematurity, and disordered behavior in children (baby blues), One of the non-pharmacological techniques for lowering it is prenatal yoga. Prenatal yoga has a positive impression for mothers who are pregnant because it reduces stress, I don't think so comfortable, painful moments pregnant, and painful labor. Study This study aims to determine the effect of prenatal yoga on declining maternal anxiety in the third trimester of pregnancy. The research methods carried out are qualitative with studies, references, or a literature review with a narrative review, and the approach used in a search article using PICO. The search article was done using Google Scholar, PubMed, ScienceDirect, EBSCO, and the National Library databases. Search result article from the entire database as many as 9,338, however, after selected with criteria inclusion and exclusion, 8 journals were obtained for review. From the 8 journals selected, the average respondent showed a decline in scale worry. The results of a review of 8 journals selected explained that there is an effect of prenatal yoga on declining maternal anxiety in pregnant women, with an average p-value of 0.000 (p<0.05). The effective duration of prenatal yoga is two times a week, and the most effective exercises are is technique Respiratory deep breathing, stretching muscle, and meditation.